Prevalence and Antimicrobial Resistance of Campylobacter coli and Campylobacter jejuni Isolated from Pig Guts, Pig Feces, and Surface Swabs from the Cutting Tables at Slaughterhouse and Taverns in Southern Benin - Alidehou Jerrold Agbankpe; Sylvain D. Kougblenou; Tamegnon Victorien Dougnon; Alida Oussou; Elodie Gbotche; Charles Hornel Koudokpon; Brice Boris Legba; Lamine Baba-Moussa; Honore Sourou Bankole (International Journal of Microbiology)
Campylobacter food-borne infections are a serious public health problem. In Benin, there is a proliferation of pork consumption in several forms. This study aims to determine the prevalence and the antimicrobial resistance of Campylobacter coli and Campylobacter jejuni strains isolated from pig guts, pig feces, and surface swabs from the cutting tables in southern Benin. For this purpose, 200 samples of pig guts, 40 samples of swabs from the cutting table surface, and 8 samples of pig feces were collected and subjected to bacteriological examination. The method used for the identification of bacteria was microbiological culture combined with molecular identification by PCR. The identified strains were then subjected to antibiotic susceptibility testing according to the methodology recommended by the EUCAST. Antibiotic profiles were compared between strains isolated from pig guts, pig feces, and cutting table surfaces on the one hand and among the different sampling sites on the other hand. The results obtained show that 47.6% of the samples analyzed were contaminated by Campylobacter spp. Molecular identification revealed 34.7% of Campylobacter coli and 9.3% of Campylobacter jejuni. The study of antimicrobial susceptibility showed resistance to ciprofloxacin, 44% to ampicillin, 23.9% to erythromycin, 11% to gentamicin, and 10.1% to amoxicillin + clavulanic acid. In total, 90.8% of the isolated Campylobacter strains were multidrug resistant. The use of antimicrobials in livestock production systems has increased considerably, which could explain, at least partially, the prevalence of Campylobacter and the resistance of strains to antibiotics. To limit the risk of Campylobacter food-borne infections, it is therefore important to include Campylobacter in the list of pathogens to be tested during sanitary quality control of meat and meat products in Benin.